Intracytoplasmic Sperm Injection Indications: How Rigorous? - Babayev, Samir N.; Park, Chan Woo; Bukulmez, Orhan (Seminars in Reproductive Medicine, 2014)
Up to 15% of all couples of reproductive age are diagnosed with subfertility and about one-third of those will have male factor infertility as a contributing factor. Intracytoplasmic sperm injection (ICSI) has proven to be invaluable for couples with severely compromised semen parameters. Since its introduction into the clinical practice in 1992, the indications for ICSI were dramatically expanded to include various patient populations with normal or mildly abnormal semen parameters. Moreover, some fertility programs choose to perform ICSI for all of their patients needing assisted reproductive technologies. By all means, the male factor indications for ICSI are not well defined, apart from its absolute utility with surgically obtained spermatozoa in the presence of low motility, or in cases of severe defects with sperm concentration and motility. Based on current evidence, ICSI is not indicated for routine use. Its adoption for previous history of total fertilization failure, in vitro oocyte maturation, cryopreserved oocytes, polyploidy prevention, poor-quality oocytes, diminished ovarian reserve, and advanced reproductive age are not supported by current evidence, albeit further research with well-designed studies is warranted. Finally, from a biological standpoint ICSI is considered to be more invasive, more energy consuming for the oocyte itself and its adverse genetic and epigenetic effects cannot be ruled out. Although more studies are needed to clarify definitive indications for ICSI, many of its current applications can be deemed empiric at this time.
Keywords: intracytoplasmic sperm injection; ICSI; in vitro fertilization; IVF; conventional IVF; assisted reproductive technology; ART; indications